2006
DOI: 10.1007/s00425-006-0450-6
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen peroxide production is an early event during bicarbonate induced stomatal closure in abaxial epidermis of Arabidopsis

Abstract: The presence of 2 mM bicarbonate in the incubation medium induced stomatal closure in abaxial epidermis of Arabidopsis. Exposure to 2 mM bicarbonate elevated the levels of H(2)O(2) in guard cells within 5 min, as indicated by the fluorescent probe, dichlorofluorescein diacetate (H(2)DCF-DA). Bicarbonate-induced stomatal closure as well as H(2)O(2) production were restricted by exogenous catalase or diphenylene iodonium (DPI, an inhibitor of NAD(P)H oxidase). The reduced sensitivity of stomata to bicarbonate an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
59
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(62 citation statements)
references
References 42 publications
2
59
0
1
Order By: Relevance
“…Our results are also consistent with recent studies that suggested that elevated [CO 2 ] can increase ROS production in vivo. For example, the bicarbonate-induced stomatal closure in epidermal peels of Arabidopsis was shown to be the result of increased H 2 O 2 production in guard cells (Kolla et al 2006;Kolla et al 2007). Likewise, Cheeseman (2006) found that leaves of soybean plants grown at elevated [CO 2 ] had higher levels of H 2 O 2 compared to plants at ambient [CO 2 ], although measurement of tissue H 2 O 2 content can be difficult and problematic (Queval et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…Our results are also consistent with recent studies that suggested that elevated [CO 2 ] can increase ROS production in vivo. For example, the bicarbonate-induced stomatal closure in epidermal peels of Arabidopsis was shown to be the result of increased H 2 O 2 production in guard cells (Kolla et al 2006;Kolla et al 2007). Likewise, Cheeseman (2006) found that leaves of soybean plants grown at elevated [CO 2 ] had higher levels of H 2 O 2 compared to plants at ambient [CO 2 ], although measurement of tissue H 2 O 2 content can be difficult and problematic (Queval et al 2008).…”
Section: Resultsmentioning
confidence: 99%
“…They consist in non-fluorescent molecules that become fluorescent when oxidised by ROS, and the emitted fluorescence can be observed by fluorimetry and/or by fluorescent microscopy, an advantage of such probes (Benikhlef et al, 2013;Bulgakov et al, 2012;Fester and Hause, 2005;Guo et al, 2010;Kolla et al, 2007;L'Haridon et al, 2011;Li et al, 2007;Liu et al, 2010;Ma et al, 2013;Peleg-Grossman et al, 2012;Plancot et al, 2013;Tada et al, 2004;Wen et al, 2008;Ye et al, 2013). Luminol or luminol analogues are sensitive chemiluminescent probes used to quantify a relative intensity of ROS by counting the emitted light with a luminometer, CDD camera or a scintillation counter (Dubreuil-Maurizi et al, 2010;Flury et al, 2013;Kunz et al, 2006;L'Haridon et al, 2011;Mersmann et al, 2010).…”
Section: Detection Of Rosmentioning
confidence: 99%
“…Abaxial (lower) epidermal strips of Arabidopsis, tomato (Solanum lycopersicum), and Brassica napus were adhered to glass cover slips using Telesis V adhesive (Premiere Products) and subsequently treated as previously described (Kolla et al, 2007). The epidermal strips incubated with various phytohormones were irradiated with white light for 2 h. The width of the stomatal aperture was measured by light microscope (Nikon OPTIPHOT 2) using a precalibrated ocular micrometer.…”
Section: Stomatal Aperture Measurementsmentioning
confidence: 99%